Pengaruh Tingkat Kompetensi Terhadap Kinerja Pegawai Administrasi Perkantoran - Lucia Nurbani Kartika; Agus Sugiarto (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2014)
One big concern towards staff competency level is by doing a comprehensive research, every organization should know how its real staff competency level, its related factor, and also the impact of competency level towards staff performance. In this research result, the variable of education background does not affect the competency level. Meanwhile working experience variable has positive relationship towards competency level. Moreover, it is proven that there is a significant difference in competency level between staffs who have ever joined trainings and those who have never joined trainings. While staffs who have office administrative and secretarial education background have better competency level compared to those who do not have similar education background. The research result shows that office administrative staff’s competency significantly affects staffs’ performance. This research is expected to be able to give exact description on how far the staff competency level of Satya Wacana Christian University administrative staffs, also to identify the related factors towards staff competency level and its relationship with their working performance. The result is expected to give contributions to human resources management of Satya Wacana Christian University (UKSW) in developing and improving the human resources quality especially administrative staff of UKSW.